PENGEMBANGAN MODUL BERBASIS PENDEKATAN SAINTIFIK KOMPETENSI DASAR MENDESKRIPSIKAN PENGERTIAN PERTEMUAN/RAPAT KELAS XI APK 2 SMK NEGERI 2 NGANJUK - FERI ANDRIAN UMBARAN, RHENDY (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2015)
ABSTRACT   Modules are systematic arranged materials teaching using language that is easy to understand by students according to the level of their knowledge, so that they can learn independently. Therefore, the modules must be arranged appropriately based on the basic competencies and applicable curriculum. This research aims to determine the module development process, the feasibility of the module and the students’ responses to the basic competency scientific approach module-based which was used to describe the meaning of a class meeting that has been developed in SMK Negeri 2 Nganjuk. The type of this research is the development research or research and development (R & D) using 4-D model of the development of models define (defining), design (designing), development (developing) and disseminate (spreading). The subjects of this research are 16 students of 11th grade in SMK Negeri 2 Nganjuk. Based on the module feasibility analysis result by the validator that based on the components of content, presentation, chart, and linguistic obtained the percentage average of 85.15% with a very worthy assessment interpretation criteria. While the results of students’ responses showed the percentage average of 92.48% with a very well criteria. So, it could be concluded that the scientific approach modules-based has been developed very worthy to serve as teaching materials in SMK Negeri 2 Nganjuk. Key words: modules development, describing the meaning of a meeting, scientific approach